2019
DOI: 10.1177/0300060519845807
|View full text |Cite
|
Sign up to set email alerts
|

Potential of modified puncture method to decrease intravenous indwelling needle-related complications in inpatients with cardiovascular disease

Abstract: Objective This study was performed to investigate the potential of a modified puncture method to decrease the incidence of intravenous indwelling needle-related complications in inpatients with cardiovascular disease. Methods From February 2017 to July 2017, 436 consecutive inpatients with cardiovascular disease requiring infusion treatment were recruited and randomly divided into the control group and the treatment group. The standard infusion puncture method was applied in the control group, and a modified p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For blood vessels that are poorly visible to the naked eye, nurses can apply this new technology to solve the problem, which can not only effectively increase the success rate of a puncture but can reduce puncture complications It also greatly reduces the discomfort of patients, doctor-patient disputes, and workload. However, the operator's proficiency in the use of ultrasound is also an important factor in determining the puncture time and the incidence of complications (12). In the clinical setting, a number of steps must be followed.…”
Section: Discussionmentioning
confidence: 99%
“…For blood vessels that are poorly visible to the naked eye, nurses can apply this new technology to solve the problem, which can not only effectively increase the success rate of a puncture but can reduce puncture complications It also greatly reduces the discomfort of patients, doctor-patient disputes, and workload. However, the operator's proficiency in the use of ultrasound is also an important factor in determining the puncture time and the incidence of complications (12). In the clinical setting, a number of steps must be followed.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is effective in avoiding pain caused by repeated puncture, protecting the patients' blood vessels to a certain extent, and improving the patients' comfort level during treatment [1] . Existing research have suggested that the success rate of indwelling needles for patients benefited from the safe and effective improvement of indwelling time for patients as well as the reduction of discomfort caused by repeated punctures [4] . In this study, the effectiveness of QCCs for indwelling needle was assessed by comparing the indwelling needle duration and performing a fishbone analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the success of the re-entry process, this kind of indwelling needle tends to cause exudation. Currently, the puncture technique in clinics has garnered increasing attention and has been the focus of primary training for nurses; even routine standard maintenance training is considered inferior to it [6] . However, regular and standardized maintenance is extremely important to improve the success rate of indwelling needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widely used intravenous indwelling needle is a good framework for the construction of CTCs enriching device due to its long indwelling time in vessel. [16] The catheter is made of polyurethane, which can be covalently modified with tumor specific antibodies, enabling capture of CTCs from the whole-body blood continually with the aid of circulation.…”
Section: Introductionmentioning
confidence: 99%